English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-09-18 13:25:36 · 3 answers · asked by jilljeter2004 1 in Science & Mathematics Mathematics

3 answers

Use the Chain Rule: let u = 8x^2 + x; du/dx = 16x+1

y = u^7; dy/du = 7u^6

dy/dx = dy/du x du/dx = 7u^6 (16x+1) = 7(8x^2+x)(16x+1)

2006-09-18 13:29:52 · answer #1 · answered by hayharbr 7 · 0 0

f'(x) = [7(8x^2 + x)^6] (16x +1)

2006-09-18 13:30:55 · answer #2 · answered by Anonymous · 0 0

7*(8x^2+x)^6*(16x+1)

2006-09-18 13:29:42 · answer #3 · answered by bruinfan 7 · 0 0

fedest.com, questions and answers